2015
DOI: 10.1007/s12011-015-0250-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cadmium Exposure Reduces the Local Angiotensin I Converting Enzyme Activity and Increases the Tissue Metal Content

Abstract: Cadmium exposure causes health problems that may result from increased oxidative stress and from changes in enzyme metalloproteases activities as angiotensin-converting enzyme (ACE). In fact, cadmium produces inhibition of serum ACE but is not known how cadmium acts on tissue ACE activity and whether following acute exposure tissue cadmium content is increased. In order to elucidate these issues, a cadmium bolus was injected intravenously in Wistar rats, and the cadmium content and the ACE activity were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
2
1
1
Order By: Relevance
“…Studies showed that one of the possible mechanism associated with hypertension development is disruption of the renin-angiotensin system which plays a major role in blood pressure regulation. 24 The result of cadmium-induced hypertension is in agreement with a study done by Angeli et al (2013) which demonstrated that acute exposure to Cd undoubtedly caused endothelial dysfunction by a mechanism relating to increased local release of angiotensin II, increased activity of COX-2, and NADPH oxidase. These mechanisms could contribute to the development of hypertension and atherosclerosis.…”
Section: Discussionsupporting
confidence: 87%
“…Studies showed that one of the possible mechanism associated with hypertension development is disruption of the renin-angiotensin system which plays a major role in blood pressure regulation. 24 The result of cadmium-induced hypertension is in agreement with a study done by Angeli et al (2013) which demonstrated that acute exposure to Cd undoubtedly caused endothelial dysfunction by a mechanism relating to increased local release of angiotensin II, increased activity of COX-2, and NADPH oxidase. These mechanisms could contribute to the development of hypertension and atherosclerosis.…”
Section: Discussionsupporting
confidence: 87%
“…Aluminium and other metals such as silica, barium, cobalt and gold have earlier been implicated in the development of granulomatous lung disease that mimics sarcoidosis (Newman, 1998;Fireman et al 2016;Bajer et al 2020;Judson 2020). Though the Cd group had a non-significantly elevated ACE activity, the findings in this study are in contrast to that reported by Broseghini-Filho et al, (2015) which noted a reduction in the serum concentration of ACE after acute cadmium exposure but agrees with Júnior et al, (2020) that reported a similar result stating an increase in serum ACE levels in mice exposed to Cd only. The increases signifies that the renin-angiotensin system plays an important role in the toxicity of the cardiovascular system and therefore may also promote the progression of hypertension.…”
Section: Resultscontrasting
confidence: 71%
“…The inhibition was proposed to be via competitive replacement of zinc at the active site of ACE [24]. Furthermore, Carmignani et al [25] reported an increase in the activity of ACE following acute lead exposure, a result which is also consistent with the ndings of Shari et al [26].…”
Section: Discussionsupporting
confidence: 66%